2020
DOI: 10.1155/2020/3042636
|View full text |Cite
|
Sign up to set email alerts
|

10-HDA Induces ROS-Mediated Apoptosis in A549 Human Lung Cancer Cells by Regulating the MAPK, STAT3, NF-κB, and TGF-β1 Signaling Pathways

Abstract: 10-Hydroxy-2-decenoic acid (10-HDA), also known as royal jelly acid, has a variety of physiological functions, and recent studies have shown that it also has anticancer effects. However, its anticancer mechanisms have not been clearly defined. In this study, we investigated the underlying mechanisms of 10-HDA in A549 human lung cancer cells. We used Cell Counting Kit-8 assay, scratch wound healing assay, flow cytometry, and western blot analysis to investigate its apoptotic effects and underlying mechanism. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 47 publications
(15 reference statements)
1
16
0
Order By: Relevance
“…Considering scarce data on the effects of royal jelly or 10H2DA on anti- and promigratory/invasive marker expression in colorectal carcinoma cells, we found similar response of this fatty acid in human lung cancer cells, where it inhibited migration by upregulating E-cadherin and downregulating N-cadherin, vimentin and Snail ( 33 ). Melittin, another component of bee products, bee venom, showed the ability to downregulate β-catenin mRNA level, concurrently upregulating E-cadherin and lowering β-catenin in pancreatic adenocarcinoma cells ( 34 ), which is consistent with our results, especially in SW-480 cells.…”
Section: Results and Discusionmentioning
confidence: 79%
“…Considering scarce data on the effects of royal jelly or 10H2DA on anti- and promigratory/invasive marker expression in colorectal carcinoma cells, we found similar response of this fatty acid in human lung cancer cells, where it inhibited migration by upregulating E-cadherin and downregulating N-cadherin, vimentin and Snail ( 33 ). Melittin, another component of bee products, bee venom, showed the ability to downregulate β-catenin mRNA level, concurrently upregulating E-cadherin and lowering β-catenin in pancreatic adenocarcinoma cells ( 34 ), which is consistent with our results, especially in SW-480 cells.…”
Section: Results and Discusionmentioning
confidence: 79%
“…In addition, in the study conducted by Filipi et al (2015), it has been proven that 10-HDA had a potent anti-proliferative effect at the concentration of 37.5 µmol/mL against human colorectal adenocarcinoma cells [20]. Recently, Lin et al (2020) have revealed the promising in vitro anticancer effects of 10-HDA against human lung cancer cell lines of A549, NCI-H460, and NCI-H23with IC 50 values of 22.68, 44.03, and 44.79 µM, respectively, whereas it had no significant cytotoxicity on IMR90 human normal lung fibroblasts [21].…”
Section: Groupmentioning
confidence: 99%
“…It has been proven that one of the most important strategies for cancer treatment is inhibiting cancer cell migration; on the other hand, the TGF-β1 signaling pathway has been proven to modulate various physiologic processes, including proliferation, migration, and invasion of tumors [21]. Lin et al (2020) have revealed that 10-HDA through downregulation of TGF-β1, SANI 1, GSK-3β, N-cadherin, and vimentin affects signal transduction pathways in A549 cells, so that the cells could not proliferate normally, limiting their range of activities, and thereby inhibiting the migration of lung cancer cells.…”
Section: Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…10-Hydroxy-2-decenoic acid (10-HDA), also known as royal jelly acid, is the major fatty acid component of royal jelly. 10-HDA has been reported to possess a variety of activities beneficial to human health, including anti-inflammatory [ 19 , 20 ], antitumor [ 21 , 22 , 23 ], immunomodulatory [ 24 , 25 ], and lifespan-extending activities [ 26 ]. We have previously reported that 10-HDA has an antibacterial activity against planktonic S. aureus by destroying the integrity of the cell membrane [ 27 ].…”
Section: Introductionmentioning
confidence: 99%